Analisis Kinerja Saham LQ-45 Pada PILKADA DKI Jakarta Putaran II 2017 - Moh. Zaki Kurniawan (Universitas Islam Balitar, 2019)
The purpose of this study is to see the differences in the performance of LQ-45 shares before and after the Jakarta Election in the second round of 2017 through returns, abnormal returns, and cumulative abnormal returns on the Indonesia Stock Exchange.This study uses purposive sampling in the LQ 45 index. This type of research is an event study. The research period for 20 days: 10 days before and 10 days after event. Hypothesis testing uses paired sample t-test. Paired sample t-test test results showed the stock return did not differ before and after the period. The results of paired sample t-test abnormal return and cumulative abnormal return before and after the election were found to be no difference.